A novel wireless visual sensor network protocol based on LoRa modulation. (March 2018) - Fan, Chunlei; Ding, Qun
At present, aiming at complexity of topology and limited network coverage for wireless visual sensor networks so that partial application cannot be implemented. Considering this situation, a novel low-power wide area network protocol is proposed with the purpose of overcoming this disadvantage, which combines LoRa modulation technique with embedded microprocessor technology. This protocol has the advantages of low power consumption, wide coverage, good extensibility, and simple topological structure. This protocol applies to the related fields such as intrusion detection for video intelligent monitoring, which has certain reference significance to research in the wireless visual sensor network field.